Concurrent Angiomyolipoma and Clear Cell Renal Cell Carcinoma in the Same Kidney: A Rare Finding in a Patient without Tuberous Sclerosis - Amal Fekkar; Kaoutar Znati; Fouad Zouaidia; Hafsa Elouazzani; Zakia Bernoussi; Ahmed Jahid (Case Reports in Urology)
Synchronous renal cell carcinomas (RCC) and angiomyolipomas (AML) occurring in the same kidney are rare. Cases in the setting of tuberous sclerosis (TS) have been reported in the literature. However, the association of these tumors in the same kidney without TS is even more rare. We report here a case of a clear cell renal cell carcinoma (CCRCC) associated with an AML in the same kidney in a 42 years old female lacking the TS diagnostic criteria. The patient underwent a radical nephrectomy. Six months after surgery, the patient is healthy without signs of tumor recurrence or distant metastasis.